Charles Olson changes objects: a reinterpretation of projective verse. Issue 7 (9th August 2019) - Marshall, Alan
ABSTRACT: This article argues that what Charles Olson called objectism was not the mere rehashing of objectivist poetics, as has sometimes been supposed, but involved the working out of a position that was diametrically opposed to objectivism, with respect both to objects in the world and objects in the poem. Central to objectism was what I call here the rule of interchangeability. It is this principle of interchangeability, I argue, that both grounds poetry's open form and frees up its dynamic relational energy. In the second half of the essay, I consider how these findings bear upon the poetry through a detailed close reading of some of the earlier Maximus poems.